2022
DOI: 10.1017/s0022215122000470
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the risk of neoplasia associated with unilateral maxillary sinus opacification on computed tomography

Abstract: Background Unilateral maxillary sinus opacification on computed tomography may reflect an inflammatory or neoplastic process. The neoplasia risk is not clear in the literature. Methods In this retrospective study, computed tomography sinus scans performed over 12 months were screened for unilateral maxillary sinus opacification, and the rates of inflammatory and neoplastic diagnoses were calculated. Results Of 641 computed tomography sinus scans, the rate of unilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It could be due to sustained release of inflammatory mediator by tumour cell. Some authors [ 28 ] suggested that high inflammatory cell population may help to predict IP recurrence or apparent malignant transformation. However, the correlation of IP recurrence and persistent inflammation need be further studied because of smaller sample in present study.…”
Section: Discussionmentioning
confidence: 99%
“…It could be due to sustained release of inflammatory mediator by tumour cell. Some authors [ 28 ] suggested that high inflammatory cell population may help to predict IP recurrence or apparent malignant transformation. However, the correlation of IP recurrence and persistent inflammation need be further studied because of smaller sample in present study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our study revealed that of the 85 patients who were afflicted, 52 (61.1%) were men and 33 (38.9%) were women, making up the bulk of the patient population. According to multiple studies that have shown a 56% frequency of bone erosion in AFRS, African American men are reportedly 15 times more likely to be affected than Caucasians and African American women combined (22) .…”
Section: Discussionmentioning
confidence: 99%